2022
DOI: 10.3389/fpubh.2022.808264
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Assets, Self-Control and Internet Gaming Disorder in Adolescence: Testing a Moderated Mediation Model in a Longitudinal Study

Abstract: From the perspective of positive youth development, developmental assets and self-control play critical roles in promoting adolescent development. However, their effects have not been evaluated in the current issue, internet gaming disorder (IGD). IGD is gradually becoming an important social problem among worldwide youth and has been included in the eleventh International Classification of Diseases (ICD-11). Therefore, the present study was determined to investigate the relationship between developmental asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 65 publications
5
19
1
Order By: Relevance
“…And this finding enriched the previous studies by directly confirming the cumulative effects of 15 positive attributes on cyberbullying ( 34 , 35 , 37 ) and empirically responded to Schiamberg et al's advocacy ( 31 ) to incorporate PYD theory to investigate bullying behaviors. Additionally, this finding echoes the studies of Xiang et al ( 28 ) and Gan et al ( 38 ) which revealed the cumulative effects of various developmental assets on reducing Chinese adolescents' IGD. And this current finding also expanded the indirect evidence on relation between several positive attributes and IGD, as well as other forms of addiction ( 41 44 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…And this finding enriched the previous studies by directly confirming the cumulative effects of 15 positive attributes on cyberbullying ( 34 , 35 , 37 ) and empirically responded to Schiamberg et al's advocacy ( 31 ) to incorporate PYD theory to investigate bullying behaviors. Additionally, this finding echoes the studies of Xiang et al ( 28 ) and Gan et al ( 38 ) which revealed the cumulative effects of various developmental assets on reducing Chinese adolescents' IGD. And this current finding also expanded the indirect evidence on relation between several positive attributes and IGD, as well as other forms of addiction ( 41 44 ).…”
Section: Discussionsupporting
confidence: 87%
“…In response to this policy call and considering that these online behavioral problems have high prevalence and critical adverse effects ( 2 , 5 , 7 , 8 ), this study attempts to figure out protective factors that could significantly prevent adolescents from these problems. Theoretical and empirical evidence suggests that PYD attributes are tightly linked to cyberbullying and IGD ( 20 , 28 , 34 , 35 ), but the underlying mechanism is still unknown. Thus, the current study investigated the interactions between cyberbullying and IGD as well as the buffering effects of PYD attributes among Chinese adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to social control theory ( 72 ), a favorable school environment helps students develop “bonds” and social norms that limit their offending behavior, such as the IGD. Xiang et al ( 73 ) found that developmental assets, incorporating school assets, negatively predicted adolescent IGD through a longitudinal study. In a study of 500 Chinese students ranging from 12 to 17 years old, Yu et al ( 74 ) showed that school climate could alleviate their problematic online game use.…”
Section: Introductionmentioning
confidence: 99%